Optimization of solutions of a linear control system - Valeyev, K. G.; Lapshin, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We suggest a new method for optimizing solutions of a linear control system, which is based on the solution of the Lyapunov matrix equation.